Oral health education program among pre-school children: an application of health-promoting schools approach - Mahboube Shirzad; Mohammad Hossein Taghdisi; Tahere Dehdari; Jamile Abolghasemi (Tabriz University of Medical Sciences, 2016)
Background: Preschool children have a limit ability to take care of their teeth. The aim of this study was to determine the effect of an intervention based on Albanian's Health Promoting Schools Model (Albanian's HPSM) on the oral health behaviors among a group of Iranian female preschool (5-6 years old) children. Methods: In this quasi-experimental study, 120 children in seventh district of Tehran, Iran were randomly recruited and assigned to either the intervention or the control groups. A scale was designed and validated to assess the oral health behaviors among the children and knowledge,attitude, self-efficacy beliefs, perceived barriers and oral health behaviors among the parents and the schoolteachers. An expert panel approved the content validity of the scale (CVR = 0.89,CVI = 0.90). The reliability was also approved applying intraclass correlation coefficient (range,0.83-0.92) and Cronbach alpha (range, 0.83-0.96). Based on the preliminary data, a 6-week intervention was designed and conducted to the intervention group. One month following the intervention, both groups were followed-up. The data were analyzed using covariance and paired t tests. Results: Following the intervention, significant differences were found in the oral health behaviors of the children in the intervention group (P < 0.05) and knowledge, attitude, oral health behaviors, self-efficacy, and perceived barriers of their parents and the schoolteachers(P < 0.05). Conclusion: Using Albanian's health-promoting schools (HPSs) approach was useful in improving the oral hygiene behaviors among the preschool children.